MitoCarta3.0: an updated mitochondrial proteome now with sub-organelle localization and pathway annotations. Issue Volume 49:Issue D1(2021) (11th November 2020) - Rath, Sneha; Sharma, Rohit; Gupta, Rahul; Ast, Tslil; Chan, Connie; Durham, Timothy J; Goodman, Russell P; Grabarek, Zenon; Haas, Mary E; Hung, Wendy H W; Joshi, Pallavi R; Jourdain, Alexis A; et al.
Abstract: The mammalian mitochondrial proteome is under dual genomic control, with 99% of proteins encoded by the nuclear genome and 13 originating from the mitochondrial DNA (mtDNA). We previously developed MitoCarta, a catalogue of over 1000 genes encoding the mammalian mitochondrial proteome. This catalogue was compiled using a Bayesian integration of multiple sequence features and experimental datasets, notably protein mass spectrometry of mitochondria isolated from fourteen murine tissues. Here, we introduce MitoCarta3.0. Beginning with the MitoCarta2.0 inventory, we performed manual review to remove 100 genes and introduce 78 additional genes, arriving at an updated inventory of 1136 human genes. We now include manually curated annotations of sub-mitochondrial localization (matrix, inner membrane, intermembrane space, outer membrane) as well as assignment to 149 hierarchical 'MitoPathways' spanning seven broad functional categories relevant to mitochondria. MitoCarta3.0, including sub-mitochondrial localization and MitoPathway annotations, is freely available at http://www.broadinstitute.org/mitocarta and should serve as a continued community resource for mitochondrial biology and medicine.